Evolutionary tendencies of bullying as a form of ostracism in the educational environment - Nazarevich , Viktoria (Psychological Prospects Journal, 2021)
Purpose. Priority is given to the study of the issue of psychological harassment in the educational space, the solution of which largely depends on the goals and selected strategies of its theoretical study, as well as the means of empirical research. Methods. For research of factors of passing to the tendencies of ostrakization as exit from bullying-strategies an empiric study in that methodology of the valued orientations of M. Rokych for the exposure of features of behavioral elections and values of personality of ostracizer and methodology was used "Diagnostics of motivation to success" of E. Ehlers was undertaken in educational space, for research of age-old changes of motivation of participants of group of ostracizers in educational, on the basis of results of that the analysis of the obtained analytical data is carried out. Results. The main mechanism of the origin of ostracism, which is defined as the expansion of individual models of socially acceptable stereotypical behavior of bullies in different types of interaction and stressful situations, is described. The classification of the main mechanisms of passive overcoming of active manifestations of aggression is formed, on the basis of which the factors of transition to tendencies of ostracism as a way out of bullying strategies in educational space are presented: education / punishment; loss of curiosity as a form of evolution of personality value orientations; submission of the; submission of the victim; age-related changes in motivation. Conclusions. Conclusions are made in the system of studying the evolutionary tendencies of bullying as a form of ostracism in the learning environment that the individual-ostracizer can have a high level of communication (as inclusion in all processes of group life and the possibility of personal influence on its course) value; formation of the personality of the ostracizer in the senior school and student age may be the consequence of a high level of claims of the individual and possible display of a syndrome of "excellent student"; the level of personal and social responsibility increases the level of motivation for the success of individuals and also involves the use of latent forms of aggressive behavior as a manifestation of ostracizing tendencies.